Impact of Humour-based ESL Teaching on the Speaking Skills of Pakistani ESL Learners - Zaka ur Rehman; Ahmed Raza ur Rehman; Shafaq Sohail (JELLL, 2024)
English is a global lingua franca and has become necessary for everyone to learn it. In Pakistan, there is a need to find the ways and means to make this learning process easy and enjoyable. The present study explores the use of humour-based material to improve the speaking skill of Pakistani ESL learners. Although research on humour is growing across the globe (Farahani & Abdollahi, 2018) but in the context of Pakistan limited studies have been conducted in this regard. Humour, if included in teaching, helps the learners to learn with less conscious effort (Nayyar & Zeeshan, 2017). This study used IHPT and focused on understanding how humour-based teaching material affects the speaking skill of learners. A quasi-experimental design with two intact classes of Bachelor of Science comprising 30 students each was adopted in the study. By using an IELTS speaking test, a pretest was conducted and the post-test was conducted after the 10 weeks of treatment. The results show that the students in the experimental group improved their speaking in terms of fluency, lexical resources, and pronunciation while the improvement in grammatical range of both the groups was not significantly different.